Assessment of OGC web processing services for REST principles. (6th January 2015) - Granell, Carlos; Díaz, Laura; Tamayo, Alain; Huerta, Joaquín
Recent distributed computing trends advocate the use of REpresentational State Transfer (REST) to alleviate the inherent complexity of the web services standards in building service-oriented web applications. In this paper we focus on the particular case of geospatial services interfaced by the OGC web processing service (WPS) specification in order to assess whether WPS-based geospatial services can be viewed from the architectural principles exposed in REST. Our concluding remarks suggest that the adoption of REST principles, to specially harness the built-in mechanisms of the HTTP application protocol, may be beneficial in scenarios where ad hoc composition of geoprocessing services are required, common for most non-expert users of geospatial information infrastructures.